Case Report: Laparoscopic repair of a recurrent, huge, inguinoscrotal vesicoureteral hernia: a case report and review of the literature - Tian, Shunhua; Min, Guilin; Yang, Fan; Tan, Qingfeng; Chen, Hongliu (Frontiers in Surgery, 2025)
Inguinal hernia repair is a routine operation. However, it is rare for the organs of the urinary system to prolapse as the contents of the hernia. An 80-year-old obese male with a history of three prior open inguinal hernia repairs presented with a recurrent large scrotal mass and severe right hydronephrosis. Preoperative Computed Tomography urography (CTU) revealed a giant inguinal vesicoureteral hernia involving the bladder and ureter. The patient underwent transabdominal preperitoneal repair (TAPP) with intraoperative identification of herniated bladder-ureter components facilitated by bladder catheter saline infusion and ureteroscopic assistance. Postoperative CTU at 1 week demonstrated complete reduction of herniated viscera and resolution of hydronephrosis. No complications occurred, and 6-month follow-up confirmed sustained recovery without recurrence. This case provides valuable insight into preoperative diagnostic difficulties and the intra- and postoperative management of an inguinal vesicoureteral hernia in a multiple relapsed old man, highlighting the importance of accurate diagnosis and appropriate surgical intervention in the treatment of this disease.